ВЛИЯНИЕ АСИММЕТРИЧНОСТИ ИНФОРМАЦИИ НА РАЗВИТИЕ РЫНКА НЕФТЕПРОДУКТОВ В УКРАИНЕ (International Journal of Innovative Technologies in Economy, 2018)
The article analyzes the influence of information asymmetry on the development of the oil products market in Ukraine. It is shown that the artificial restriction of access to official data on prices, volumes and quality of oil products, the conclusion of informal agreements between the authorities and some market participants, the termination of financing of the state quality control system lead to an increase in the information asymmetry. The negative consequences of the information asymmetry lie in the irrational allocation of resources and the impossibility of establishing market equilibrium. The growth of information asymmetry increases the consumers' distrust of all market participants and policy-making authorities. The protection of the rights of consumers and suppliers should be based on full information about the properties, prices and quality of goods and services. Voluntary initiatives of market participants are an indispensable condition for the existence of a civilized market. If these "rules of the game" are not clearly defined, not only the consumers, but all market participants and the state will suffer.